Effectiveness of nurse-led progressive muscle relaxation on stress, anxiety, and depression in parents of adolescents with mental illness: A randomized controlled trial - Sijesh George; Radhakrishnan Govindan; John Vijay Sagar Kommu (Journal of Education and Health Promotion)
BACKGROUND: Prevention of depression, stress, and anxiety is a serious concern of the World Health Organization and has been a research topic over the last decades. There is a close association found between children’s mental health problems and parental stress, valid for biological and foster families. Evidence suggests that parents with children with disabilities are more stressed, depressed, or anxious than parents who do not have such children. In addition, the progressive muscle relaxation technique (PMR) is the easiest to learn and administer among the relaxation methods available for lowering stress, anxiety, and depression. MATERIALS AND METHODS: A randomized clinical trial (RCT) was adopted with an equivalent group pre-test and post-test design. The experimental group (n = 31) received ten sessions of Jacobson PMR, and the control group (n = 30) received treatment as usual (TAU). Data analysis: The researcher used frequency, percentage, mean, standard deviation, median, and interquartile range to describe the study subjects’ demographic profile and clinical profile. Mann-Whitney U test, Kruskal-Wallis H test, and Spearman’s Rho were used to find an association between socio-demographic and clinical variables in parents’ stress, anxiety, and depression levels. Further, Spearman’s Rho was used to find a correlation between stress anxiety and depression. In addition, the Chi-square test and Fisher’s exact test were used to compare control and experimental groups with important socio-demographic and clinical variables. Further, Fridman’s analysis of variance (ANOVA) was used to assess PMR’s effectiveness on group stress, anxiety, and depression. Finally, the Mann-Whitney U test was used to compare stress, anxiety, and depression levels between groups. RESULTS: Analysis revealed clinically and statistically significant (P < 0.05) reductions in the stress and anxiety scores of the parents after five sessions of the PMR technique. In addition, findings reveal that there is a statistically significant reduction (P < 0.001) in depression, anxiety, and stress scores after ten sessions of the PMR program among parents of adolescents with mental illness. CONCLUSION: The PMR program adopted in this study was highly effective in reducing stress, anxiety, and depression among parents of adolescents with mental illness.